Assessing student performance : exploring the purpose and limits of testing. - Wiggins, Grant P.; Wiggins, Grant P. (San Francisco : Jossey-Bass Publishers, 1993)
What is assessment and how does testing differ from it? Why will a move to performance tests, by itself, not provide us with an adequate system of student assessment? How might we better "test our tests" beyond the technical standards that now apply? And why won't increased national testing offer us the accountability of schools we so sorely need? In this book, Grant P. Wiggins clarifies the limits of testing in an assessment system. Beginning with the premise that student assessment should improve performance, not just audit it, Wiggins analyzes some time-honored but morally and intellectually problematic practices in test design, such as the use of secrecy, distracters, scoring on a curve, and formats that allow for no explanation by students of their answers. He explains how many test-design standards serve technical experts and their needs rather than students and their interests. And he discusses how useful and timely feedback is an absolute requirement of any authentic test. By showing us that assessment is more than testing and intellectual performance is more than right answers, Wiggins points the way toward new systems of assessment that more closely examine students' habits of mind and provide teachers and policy makers with more useful and credible feedback
Includes bibliographical references
Keywords: Educational tests and measurements -- United States